257 Residential exposures are associated with increased odds of SLE diagnosis. (April 2019) - Li, Jing; Trupin, Laura; Gianfrancesco, Milena A; Lanata, Cristina; Katz, Patricia; DallEra, Maria C; Yazdany, Jinoos
Abstract : Background: Environmental exposures, such as pesticides, silica, and asbestos have been associated with risk of SLE. In this study, we assessed the association between different residential exposures and SLE diagnosis in a diverse cohort of lupus participants and healthy controls. Methods: Data were from the California Lupus Epidemiology Study (CLUES), a racially/ethnically diverse cohort of SLE patients, and healthy controls with no history of autoimmune systematic diseases who resided in the San Francisco Bay Area. SLE diagnoses were confirmed through medical records and rheumatologist clinical examination. All participants completed a structured interview that included demographics (age, sex, race/ethnicity and education) and residential exposures (frequent exterminator use, other home insecticide use, kerosene for heating, and living in an agricultural area), and for SLE, disease damage (Brief Index of Lupus Damage, BILD) score and age of lupus diagnosis. Multivariable logistic regression models assessed the association of each exposure with SLE status, and linear regression models to examine the association of each exposure with disease damage (i.e. BILD score) for SLE patients, both adjusting for age, sex, race/ethnicity and education. Results: We included 359 SLE patients with an average diagnosis age of 32±11 years and 106 healthy controls. Ninety-one percent of SLE patients and 89% of controls were female. SLE patients were older than controls, with a mean age of 49±14 vs. 41±16 (p<0.05). Both groups were racially/ethnically diverse, with over 65% identified as non-White. Over half of SLE patients (56.7%) reported any exposure compared to 40% of controls (p<0.05). Specific exposures of the SLE group ranged from 8.8% for kerosene to 28.9% for agricultural exposure (see table 1 ). There was a higher prevalence of any exposures among SLE patients vs. controls (OR 1.9, 95% CI 1.2–3.0, p<0.05), as well as specific exposures to pesticides (exterminator) (OR=1.9, 95% CI 1.0–3.7), other home insecticide use (OR=2.1, 95% CI 1.1–4.1, p<0.05) and kerosene (OR=2.8, 95% CI 0.8–9.7). We found no association between residential exposures and BILD score in the SLE-only analysis. Conclusions: SLE diagnosis was associated with increased odds of residential exposures, but this study is under powered to fully examine individual exposures. Lack of information on timing of exposures is another study limitation. While this study demonstrates the prevalence of exposures, the observed trend warrants further investigation with assessments of exposure timing relative to age and SLE diagnosis. Funding Source(s): Centers for Disease Control (U01DP005120)